Ophthalmic Artery Doppler Waveform Changes Associated with Increased Damage in Glaucoma Patients - Abegão Pinto, L (2012)
PURPOSE: To characterize Doppler waveform variables (early systolic acceleration [ESA] and systolic/diastolic mean velocity ratios [Sm/Dm]) of the Ophthalmic Artery (OA) by color Doppler imaging (CDI) in eyes with primary open-angle glaucoma (POAG). METHODS: Analysis of CDI examinations of the retrobulbar circulation of patients with POAG (n = 102), normal tension glaucoma (NTG, n = 89), and healthy controls (n = 59) by a condition-masked investigator. One-way ANOVA, chi-square, and Spearman's rank correlation tests were used to determine differences, establish comparisons, and to explore associations between variables, respectively. RESULTS: The overall Doppler waveform presented a shift to the right in the glaucoma groups, with significantly lower Sm/Dm ratios when compared to the control group (healthy: 2.94 ± 0.86, POAG: 2.60 ± 0.67, NTG: 2.63 ± 0.84; P = 0.01). ESA was significantly lower in the glaucoma groups (healthy: 688.8 ± 484 cm·s(-2), POAG: 548.1 ± 419 cm·s(-2), NTG: 548.5 ± 337 cm·s(-2); P = 0.03). No statistical differences were, however, detected in the OA velocities or resistance index (P ranged between 0.08 and 0.96). In the glaucoma groups, waveform parameters such as ESA, acceleration time, and systolic mean velocities correlated with systemic blood pressure variables (P < 0.05). In these groups, negative correlations were detected between Sm/Dm ratios and the degree of visual field defects (POAG: P = 0.01; r = -0.25) and retinal nerve fiber layer thickness (NTG: P = 0.02; r = -0.25). CONCLUSIONS: The pattern of blood flow velocities in the OA throughout the cardiac cycle seems to be altered in glaucoma patients. Further studies on how systemic blood pressure affects waveform variables in glaucoma patients may provide a better understanding of an underlying vascular dysfunction.